Membangun Kepuasan Kerja Optimal dan Tinjauan Terhadap Faktor yang Mempengaruhi Evaluasi Individu Mengenai Prilaku Organisasi di “Swells Barbershop Padang” - Shafira Azhari; Salsabila Salsabila; Wahyu Agustin; Windi Gusti Ayu; Vivi Nila Sari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Barbershops have a long history dating back to Ancient Egypt and medieval Europe, where barbers also served as surgeons. Today, modern barbershops are not just places for haircuts but are integral to lifestyle and cultural identity, offering various additional services. Factors contributing to job satisfaction include good employee performance, management support, and stable emotional conditions. Effective emotion management and a positive mood significantly influence productivity and employee performance. Prioritized individual values include good attitudes, quality service, and consistency in service delivery. The implementation of these values is reflected in the daily actions of employees and management. Adapting to different coworker personalities and addressing operational issues like tardiness are also crucial aspects of creating a harmonious and productive work environment. The PBL activity is located in front of the Grand Zuri Hotel or next to Bakso Malang Mas Pepen, Jl. Thamrin No.8B, Alang Laweh, Kec. Padang Sel., Kota Padang, West Sumatra. With a deep understanding of these factors, barbershops can create better working environments and improve the quality of services provided to customers